TDL-based Wideband Beamforming for Radio Sources Close to the Array Endfire - N. Solgi (Journal of Electrical and Computer Engineering Innovations, 2015)
Uniform linear array (ULA)-based tapped-delay line (TDL) structure has good performance metrics when the signal sources are located at the middle angles. It offers poor performance when the signal sources are close to the array endfire. In this paper, a new approach is proposed which offers higher performance and desired beamforming on TDL structure when the wideband uncorrelated radio sources are close to the array endfire. This new TDL structure is based on Shirvani-Akbari array (SAA). Numerical results of this investigation show that both ULA-based and SAA-based TDL structures have the same performance where the signals of interest located at the middle angles. But, where the signals are close to the array endfire, the SAA-based TDL structure has much higher performance. In order to find a good comparison, the absolute array factor (AF) in center frequency for different angles and three well-known performance metrics, normalized mean square error (NMSE), signal to interference plus noise ratio (SINR) and bit error rate (BER) are evaluated for both ULA-based and SAA-based TDL structures.